SANKSI PIDANA BAGI PENCEMARAN NAMA BAIK DI MEDIA SOSIAL (CRIMINAL SANCTIONS FOR DEFAMATION ON SOCIAL MEDIA) - Al-Haqi, Muhammad Alifikri; Khoiru Zadit Taqwa; Dica Kurnia Dipura; Muhammad Agil Septian; Avroditha Edelweis Manihuruk (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
The development of the digitalization era which is characterized by technological developments create the development of communication and information through social media, but this development creates both positive and negative impacts. The negative impact diahasilkan of this development is the rise of good name pollution conducted through social media platforms such as Facebook, Instagram, Tiktok, Twitter and the like. Libel pollution on social media can be shaped like negative comments, slander, photo distribution or videos that do not match facts, and the spread of hoax news. Defamation in Indonesia is prohibited and can obtain sanctions as stipulated in Article 310-321 of the Criminal Code, whereas defamation in social media itself is regulated in Law Number 1 of 2024 of Law on Second Amendments to Law Number 11 of 208 concerning Electronic Law and then the EIT of Law.